Simulation and correlation of the melt flow characteristic using Polystyrene in usymmetrical cavity injection mold - Abdulla Mahmoud, Ahmed
In plastic injection molding. the problems found in the mold design stage are the capability on plastic flow and unsymmetrical cavity on the injection molding. Different thickness. morphology and volume on cavities have causes the different flow characteristic and results in different injection times. This research uses Solid-Work and Cad-Mold as Computer Aided Engineering (CAE) technology for design analysis and construction on ul/symmetrical cavity injection molding. The material used in this study in order to find the effects of the capability on plastic flow is polystyrene (PS) . The variables used in this unsymmetrical cavity injection mold consist was melt temperature. Practical injection molding is carried by BOY injection molding 22M. The injection setting parameters are recorded and used for simulation. The injected PS samples are characterized on density and mechanical properties (tensile and flexural). Temperature setting at 2 J 0 lie. 11 6 cm3/s flow rate and maximum pressure oj 614 bar achieved the highest mechanical properties. For simulation, the rheology behavior of polystyrene is characterized from melt flow index and capillary rheometer. The obtained results by the rheology testing are viscosity. shear rate and temperature shift Jactor - carreau parameters. As for simulation. Jour sensors are setup at the gate and end on each cavity. While simulation results are analyzed by a Cadmold program. The correlation between practical and simulation are made. From there. a modified mold at a cavity gate is carried out in order to get better flow and better injection products. The analysis and judgment is based on simulation results. The result shows that the modified mold achieve higher viscosity and lower shear rate for the dumbbell cavity which could better mechanical properties.